Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

Sodium selenite inhibits proliferation of lung cancer cells by inhibiting NF-κB nuclear translocation and down-regulating PDK1 expression which is a key enzyme in energy metabolism expression - Xiao Xu; Yaqin Hou; Shumeng Lin; Kai Wang; Yanbei Ren; Tiansheng Zheng; Xi Zhang; Ming Li; Lihong Fan (Journal of Trace Elements in Medicine and Biology, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.